Optimal enforcement of liveness for decentralized systems of flexible manufacturing systems using Petri nets. (August 2020) - Bashir, Muhammad
The decentralized supervisory structure has drawn much attention in recent years. Many studies are reported in the paradigm of automata while few can be found in the Petri net model. This paper proposes a new method for decentralized supervisory control using the Petri net paradigm. Two efficient Algorithms are developed in the proposed method. Algorithm 1 is used to compute decentralized working zones from the given LS 3 PR Petri net model for flexible manufacturing systems. Algorithm 2 is used to compute the decentralized controllers that enforced liveness to the decentralized working zones. The sequential assembling is used to reconnect and controlled the working zones via decentralized controllers. The decentralized controller is added to the decentralized working zones that have common elements, that is, common transitions. The proposed method has the following advantages: (i) it can be applied to a complex Petri net model for flexible manufacturing systems, (ii) the proposed methods has less computational complexity when compared with the previous methods, (iii) the proposed method can obtain a minimal number of decentralized controllers that enforce liveness of the uncontrolled Petri net model. Experimental examples are presented to explore the applicability of the proposed methods.